Antigen Detection Tests for SARS-CoV-2: a systematic review and meta-analysis on real world data - Riccò, Matteo; Ranzieri, Silvia; Peruzzi, Simona; Valente, Marina; Marchesi, Federico; Bragazzi, Nicola Luigi; Donelli, Davide; Balzarini, Federica; Ferraro, Pietro; Gianfredi, Vincenza; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2022)
Background and aim Rapid antigen detection (RAD) tests on nasopharyngeal specimens have been recently made available for SARS-CoV-2 infections, and early studies suggested their potential utilization as rapid screening and diagnostic testing. The present systematic review and meta-analysis was aimed to assess available evidence and to explore the reliability of antigenic tests in the management of the SARS-CoV-2 pandemic.Materials and Methods. We reported our meta-analysis according to the PRISMA statement. We searched Pubmed, Embase, and pre-print archive medRxiv.og for eligible studies published up to November 5th, 2020. Raw data included true/false positive and negative tests, and the total number of tests. Sensitivity and specificity data were calculated for every study, and then pooled in a random-effects model. Heterogeneity was assessed using the I2 measure. Reporting bias was assessed by means of funnel plots and regression analysis.Results. Based on 25 studies, we computed a pooled sensitivity of 72.8% (95%CI 62.4–81.3), a specificity of 99.4% (95%CI 99.0–99.7), with high heterogeneity and risk of reporting bias. More precisely, RAD tests exhibited higher sensitivity on samples with high viral load (i.e.